An explanatory factor analysis of a brief self-report scale to detect neurocognitive impairment among HIV-positive men who have sex with men and transgender women in Peru. Issue 10 (3rd October 2017) - Weikum, Damian; Shrestha, Roman; Ferro, Enrico G.; Vagenas, Panagiotis; Copenhaver, Michael; Spudich, Serena; Alpert, Michael D.; Cabello, Robinson; Lama, Javier R.; Sanchez, Jorge; Altice, Frederick L.
ABSTRACT: Neurocognitive impairment (NCI) has been associated with poor clinical outcomes in various patient populations. This study used exploratory factor analysis (EFA) to examine the factor structure of the existing 95-item Neuropsychological Impairment Scale (NIS) to create a suitable NCI screening instrument for people living with HIV (PLH). In Lima, Peru, 313 HIV-positive men who have sex with men (MSM) and transgender women (TGW) prescribed antiretroviral therapy (ART) completed the NIS using computer-assisted self-interviews (CASI). The EFA used principal axis factoring and orthogonal varimax rotation, which resulted in 42 items with an 8-factor solution that explained 51.8% of the overall variance. The revised, 8-factor, Brief Inventory of Neurocognitive Impairment for Peru (BINI-P) showed a diverse set of factors with excellent to good reliability (i.e., F 1 α = 0.92 to F 8 α = 0.78). This EFA supports the use of the BINI-P to screen for NCI among Spanish-speaking, HIV-positive MSM and TGW. Future research should examine the effectiveness of the BINI-P in detecting NCI in clinical care settings and the impact of NCI on HIV health-related outcomes, including linkage and retention in care, ART adherence and HIV risk behaviors.